Application of AERMOD model in air quality (PM10) impact assessment of selected opencast mines in The Jharia Coalfield, Jharkhand, India - Kundu, Snigdha; Kumar Pal, Asim (Oficyna Wydawnicza Politechniki Wrocławskiej, 2018)
The study mainly delineates the application of AERMOD to evaluate PM10 concentrations for the selected opencast mines in The Jharia coalfield. AERMOD estimated PM10 concentration profiles were developed on the basis of evaluated emission rates of salient coal mining activities. While comparing these estimated values with monitored values of PM10, the evaluated indices of agreement were found to be 0.86, 0.84 and 0.88 during winter and 0.94, 0.68 and 0.87 during summer for the Katrasgarh, Muraidih and Rajapur opencast mines, respectively. In a like manner, performance evaluation of AERMOD evaluated concentrations over actual field concentration using a set of five statistical tools, indicated more or less fairly good prediction for both the seasons. Further, USEPA AP-42 based emission factor data for more or less identical mining activities were also used for AERMOD run in order to evaluate PM10 profiles. Correlation analysis indicated 71–89% and 62–85% model accuracy for winter and summer, respectively.
Environment Protection Engineering. Vol. 44, 2018, nr 4, s. 5-21
Keywords: ochrona środowiska; inżynieria środowiska; czasopisma